Acceptability of virtual reality for training health professions students in serious illness communication: A cross-sectional study with educators - Aleksandrina Skvortsova; Stephanie Stiel; Kambiz Afshar; Hanna A.A. Röwer; Claudia Bausewein; Irene Hartigan; Mohamad M. Saab; Sandra Martins Pereira; Pablo Hernández-Marrero; Jan Hrdlička; Jiri Wild; Kateřina Rusinová; et al. (PEC Innovation)
Objectives: This study investigates i) acceptability, ii) predictors of intention to use, iii) barriers and facilitators, and iv) perceived advantages and disadvantages of incorporating virtual reality (VR) into serious illness communication training from the perspective of health professions educators in Europe. Methods: An online survey was distributed using snowball sampling across health professions educators involved in the creation and/or delivery of difficult communication courses (as educators, developers, coordinators). Results: Seventy-five educators from 11 European countries involved in teaching serious illness communication skills completed the survey. While educators viewed VR positively and saw it as useful, their intention to implement it was moderate, possibly, due to low compatibility with current teaching methods and social norms. Major barriers reported by participants included financial constraints (62.7 %) and lack of VR training (54.7 %), while key facilitators were training availability (22 %) and technical support (11 %). Conclusion/innovation: Educators perceive VR as a potential supplemental tool in difficult communication education; however, overcoming financial, training, and integration barriers is essential for its broader adoption and curricular integration. Further research is necessary to validate VR's effectiveness in developing the nuanced communication skills critical for serious illness communication. Innovation: VR technology is a promising innovative tool for medical communication training.